Gruppenbild mit Mendl. Wieso auf einer ikonischen Schnellfotografie Jung-Wiens Hugo von Hofmannsthal nicht zu sehen ist und wie Richard Beer-Hofmann fast die ‘Ankerbrot’-Fabrik finanziert hat: Group portrait with Mendl. Why Hugo von Hofmannsthal is not to be seen in an iconic snapshot of Young Vienna and how Richard Beer-Hofmann almost financed the ‘Ankerbrot’ factory (Studia austriaca, 2024)
The essay examines the ferrotypes taken in the Wiener Prater, featuring members of ‘Jung-Wien’, including Hermann Bahr, Richard Beer-Hofmann, Hugo von Hofmannsthal, Felix Salten, and Arthur Schnitzler. A closer examination is given to one photo, revealing that contrary to common belief, the figure depicted is not Hofmannsthal, but rather the industrialist Fritz Mendl (1864–1929).